Entrectinib in children and young adults with solid or primary CNS tumors harboring NTRK, ROS1, or ALK aberrations (STARTRK-NG). Issue 10 (8th April 2022) - Desai, Ami V; Robinson, Giles W; Gauvain, Karen; Basu, Ellen M; Macy, Margaret E; Maese, Luke; Whipple, Nicholas S; Sabnis, Amit J; Foster, Jennifer H; Shusterman, Suzanne; Yoon, Janet; Weiss, Brian D; et al.
Abstract: Background: Entrectinib is a TRKA/B/C, ROS1, ALK tyrosine kinase inhibitor approved for the treatment of adults and children aged ≥12 years with NTRK fusion-positive solid tumors and adults with ROS1 fusion-positive non–small-cell lung cancer. We report an analysis of the STARTRK-NG trial, investigating the recommended phase 2 dose (RP2D) and activity of entrectinib in pediatric patients with solid tumors including primary central nervous system tumors. Methods: STARTRK-NG (NCT02650401) is a phase 1/2 trial. Phase 1, dose-escalation of oral, once-daily entrectinib, enrolled patients aged <22 years with solid tumors with/without target NTRK1/2/3, ROS1, or ALK fusions. Phase 2, basket trial at the RP2D, enrolled patients with intracranial or extracranial solid tumors harboring target fusions or neuroblastoma. Primary endpoints: phase 1, RP2D based on toxicity; phase 2, objective response rate (ORR) in patients harboring target fusions. Safety-evaluable patients: ≥1 dose of entrectinib; response-evaluable patients: measurable/evaluable baseline disease and ≥1 dose at RP2D. Results: At data cutoff, 43 patients, median age of 7 years, were response-evaluable. In phase 1, 4 patients experienced dose-limiting toxicities. The most common treatment-related adverse event was weight gain (48.8%). Nine patients experienced bone fractures (20.9%). In patients with fusion-positive tumors, ORR was 57.7% (95% CI 36.9-76.7), median duration of response was not reached, and median (interquartile range) duration of treatment was 10.6 months (4.2-18.4). Conclusions: Entrectinib resulted in rapid and durable responses in pediatric patients with solid tumors harboring NTRK1/2/3 or ROS1 fusions.